OPTIMALISASI PEMANFAATAN MEDIA SOSIAL SEBAGAI SARANA PROMOSI UMKM PADA KAWASAN PARIWISATA DESA KUTUH - I Made Wisnu Wardana; Fahmi Tanjung; I Made Sujana; Putu Ratna Windusara Putri (Yayasan Nusantara Hasana Berdikari, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting community economic growth, particularly in tourism areas. The development of information and communication technology has shifted marketing patterns from conventional methods to digital marketing through social media platforms. However, many MSME actors in Kutuh Village still face limitations in utilizing social media as an effective promotional tool. Low digital literacy, inadequate understanding of digital marketing strategies, and limited skills in creating promotional content remain major challenges. This community service program aimed to improve the capabilities of MSME actors in optimizing social media utilization for business promotion. The methods employed included socialization, digital marketing training, promotional content creation workshops, social media mentoring, and program evaluation. The participants consisted of 35 MSME actors operating within the tourism area of Kutuh Village. The results demonstrated significant improvements in participants’ understanding of digital marketing strategies, social media account management, content creation, and the utilization of social media features to expand market reach. The program successfully enhanced the digital capacities of MSME actors and strengthened their competitiveness within the tourism sector